(untitled) (Research, Society and Development, 2022)
Ameloblastoma is a benign, aggressive, intraosseous tumor originated from the odontogenic epithelium, whose treatment ranges from more conservative approaches to total resection with safety margin. Due to the various forms of treatment for this tumor, there is a relative plurality of approaches in its management and treatment, and it is necessary to recognize the crucial points for choosing the technique. This work consists of a protocol of scope review on the different forms of treatments of individuals diagnosed with ameloblastoma developed according to the recommendations of the Joanna Briggs Institute Manual and registered in the Open Science Framework. The search for the articles will be carried out in three stages, using the PubMed databases via MEDLINE, Web of Science, Scopus (Elsevier), LILACS via VHL and Google Scholar. Publications in English, Spanish and Portuguese will be considered without a date limit. The data will be extracted through a form adapted by the authors and presented in the form of frames and/or images and descriptively, following the checklist of PRISMA-ScR. The construction of the protocol will allow a scope review with well-defined methodological steps on the theme of the treatment of patients diagnosed with ameloblastoma, allowing a greater knowledge on the subject.